Radical Scavenging Activity of Ethanolic and n-Hexane Leaf Extracts of Physalis angulata L. Using The DPPH Assay - I Made Wisnu Adhi Putra; Ni Putu Widya Astuti (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2026)
Physalis angulata L. leaves are known to have potential as a natural source of antioxidants, yet the effectiveness of extraction is highly dependent on the type of solvent used. This study aimed to compare the effects of polar solvent (ethanol) and non-polar solvent (n-hexane) on the phytochemical profile and antioxidant activity of P. angulata leaf extracts. The research methods included sample preparation of dried leaf powder, maceration extraction using ethanol and n-hexane, qualitative phytochemical screening to detect phenolics, flavonoids, terpenoids, saponins, and alkaloids, as well as antioxidant activity testing using the DPPH method to determine IC50 values. The results showed that the ethanol extract successfully detected all tested compound groups (phenolics, terpenoids, flavonoids, saponins, and alkaloids), while the n-hexane extract only detected phenolics and terpenoids. The antioxidant activity of the ethanol extract was classified as strong with an IC50 value of 87.098 ± 1.195 ppm, significantly better than the n-hexane extract which was very weak with an IC50 of 379.242 ± 7.452 ppm, and this difference was statistically significant (p < 0.0001). This study provides an important contribution by offering scientific recommendations that ethanol is the most effective solvent for extracting antioxidant compounds from P. angulata leaves, thereby serving as a reference for the development of health products and functional foods based on natural antioxidants.